Cópias arquitetônicas de Victor Dubugras: um estudo sobre cianotipia - Morais, Cristina Sanches (2022)
The context of São Paulo´s architecture in the 1890 to 1920 can be observed in the architectural projects of Victor Dubugras (1868-1933), which presents buildings with an elegant structure, constructed with materials not commonly used, such as wrought iron and glass, providing ornamentation of rounded shapes and greater lighting of the buildings´ interiors. To present his projects with the richness of details that was required and to satisfy the needs of his clients, Dubugras made use of the blueprint technique, a refined European copying process, to reproduce his drawings of house constructions in the city of São Paulo. Thus, based on John Frederick William Herschel (1792-1871) studies of cyanotype in experiments of copies of images and drawings, using paper in the process of making positive and negative copies, this research aims to analyze the various technical processes of photo reproduction brought from Europe to São Paulo by the architect Victor Dubugras; and highlight the importance of the preservation of the collection of the Architecture and Urbanism College of the University of São Paulo´s Library and the Municipal Historical Archive, where today are deposited much of Dubugras´ projects